Movement Synchrony in the Psychotherapy of Adolescents With Borderline Personality Pathology – A Dyadic Trait Marker for Resilience? - Zimmermann, Ronan; Fürer, Lukas; Kleinbub, Johann R.; Ramseyer, Fabian T.; Hütten, Rahel; Steppan, Martin; Schmeck, Klaus (Frontiers in Psychology, 2021)
Interpersonal synchrony is a fundamental process involved in resilience. Movement synchrony (MS) describes the coordination of body movements. In psychotherapy, higher MS between therapist and patient has been associated with higher levels of empathy, therapeutic alliance, better therapy outcome, and fewer drop-outs. The current study investigated MS during the psychotherapeutic treatment of female adolescents with borderline personality disorder. It was hypothesized that there are higher levels of MS in the analyzed therapy sessions compared to pseudo-interactions. Further, we tested whether higher levels of MS correlate with stronger patients’ symptom reduction and whether higher MS predicts higher post-session ratings. A total of 344 sessions with 17 completed psychotherapies of adolescent patients with BPD were analysed. MS was assessed with Motion energy analysis and an index of synchrony was calculated by lagged cross-correlation analysis. As hypothesized, the findings support higher levels of MS in therapy sessions compared to pseudo-interactions, and an association with better therapy outcome was found. Session outcome was not (patient’s perception) or negatively (therapist’s perception) associated with higher levels of MS. The relevance of MS and potential implications for clinical practice are discussed.